2017
DOI: 10.3390/jsan6040028
|View full text |Cite
|
Sign up to set email alerts
|

Wearable-Based Human Activity Recognition Using an IoT Approach

Abstract: This paper presents a novel system based on the Internet of Things (IoT) to Human Activity Recognition (HAR) by monitoring vital signs remotely. We use machine learning algorithms to determine the activity done within four pre-established categories (lie, sit, walk and jog). Meanwhile, it is able to give feedback during and after the activity is performed, using a remote monitoring component with remote visualization and programmable alarms. This system was successfully implemented with a 95.83% success ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Similarly to Kekade et al 2018 [2], we also assessed the studies' reporting of research design (Table 2), and the reported participant demography, i.e., number of participants, age, gender and the distribution of healthy participants and patients (see Sections 3.1-3.4 and Table 3). Many studies presented the participant demographics poorly, or not at all [3][4][5][6][7][8][9][10][11][12]. Rather than excluding these from the tables, we indicate missing information with a "-".…”
Section: Qualitative Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to Kekade et al 2018 [2], we also assessed the studies' reporting of research design (Table 2), and the reported participant demography, i.e., number of participants, age, gender and the distribution of healthy participants and patients (see Sections 3.1-3.4 and Table 3). Many studies presented the participant demographics poorly, or not at all [3][4][5][6][7][8][9][10][11][12]. Rather than excluding these from the tables, we indicate missing information with a "-".…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Our findings are further discussed in Section 4. [5,6] Physical activity recognition 3 ------ [7] Physical activity recognition 65…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Wearable IoT devices have been studied extensively due to their form factor and cost benefits. Researchers have proposed sensor networks, gesture-based control, health monitoring, and activity monitoring as potential applications of IoT devices [16][17][18][19][20][21][22]. Gesture recognition using wearable devices has received significant attention due to its applications in human-computer interaction, gesture-based control, and virtual reality [23][24][25][26].…”
Section: Related Workmentioning
confidence: 99%
“…As in previous studies performed by Banaee et al [37], it was found that SVM, ANN, and tree-based classifiers could be leveraged for healthcare-based uses. Additionally, Casto et al [38], showed that SVM, naïve Bayes, and ANN are potentially much more reliable when it comes to human activity detection. Therefore, for the learning process in this particular study, 5 different machine learning algorithms, namely, random forest, SVM, KNN, naïve Bayes, and ANN, were developed.…”
Section: Machine Learning Algorithm and Evaluation Metricsmentioning
confidence: 99%